2007
DOI: 10.3201/eid1304.060833
|View full text |Cite
|
Sign up to set email alerts
|

MRSA Transmission between Cows and Humans

Abstract: We isolated methicillin-resistant Staphylococcus aureus (MRSA) from cows with subclinical mastitis and from a person who worked with these animals. The bovine and human strains were indistinguishable by phenotyping and genotyping methods and were of a low frequency spa type. To our knowledge, this finding indicates the first documented case of direct transmission of MRSA between cows and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
244
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(259 citation statements)
references
References 14 publications
9
244
1
5
Order By: Relevance
“…By SCCmec typing the strains were classified as community-associated MRSA (CA-MRSA) that are characterized by the presence of smaller cassette elements of SCCmec types IV and V (Boyle-Vavra and Daum, 2007). Detection of SCCmec type IV and V in animals was also reported in other studies (Juhasz-Kaszanyitzky et al, 2007;Khanna et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…By SCCmec typing the strains were classified as community-associated MRSA (CA-MRSA) that are characterized by the presence of smaller cassette elements of SCCmec types IV and V (Boyle-Vavra and Daum, 2007). Detection of SCCmec type IV and V in animals was also reported in other studies (Juhasz-Kaszanyitzky et al, 2007;Khanna et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…All cefoxitin resistant S. aureus were also resistant to penicillin G. Out of the (77.2%) cefoxitin resistant S. aureus isolates, (95.6%) of were also resistant to Penicillin G. This is an indicator of MRSA [38][39][40]. This is due to the fact that resistance of S. aureus to these drugs may be attributed to the production of β-lactamase, an enzyme that inactivates penicillin and closely related antimicrobials [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, methicillin-resistant S. aureus (MRSA), which are resistant to almost all types of β-lactam antimicrobials, have been a concern worldwide (Lee 2003, Van Duijkeren et al 2004. The presence of MRSA in dairy cows has been investigated because it was demonstrated that cattle may serve as a source of emergence of new MRSA strains in humans (Juhász-Kaszanyitzky et al 2007, Vanderhaeghen et al 2010. Therefore, colonization of dairy cattle with antimicrobial-resistant S. aureus impacts milk production and may additionally represent an infection hazard to people who work in close contact with cows or consume raw milk (Juhász-Kaszanyitzky et al 2007).…”
Section: Introductionmentioning
confidence: 99%